A Summary of McEliece-Type Cryptosystems and their Security - Engelbert D.; Overbeck R.; Schmidt A. (Journal of Mathematical Cryptology, 2007)
In this paper we give an overview of some of the cryptographic applications which were derived from the proposal of R. J. McEliece to use error correcting codes for cryptographic purposes. Code based cryptography is an interesting alternative to number theoretic cryptography. Many basic cryptographic functions like encryption, signing, hashing, etc. can be realized using code theoretic concepts.